Differential effects of insulin sensitization and insulin provision treatment strategies on concentrations of circulating adipokines in patients with diabetes and coronary artery disease in the BARI 2D trial. (January 2016) - Wolk, Robert; Bertolet, Marnie; Brooks, Maria M; Pratley, Richard E; Sobel, Burton E; Frye, Robert L; Singh, Prachi; Calvin, Andrew D; Rutter, Martin K; Mooradian, Arshag D; Somers, Virend K; ,
Aims: To determine the effects of insulin sensitization (IS) and insulin provision (IP) treatment strategies on adipokines associated with cardiovascular disease in patients with type 2 diabetes mellitus and coronary artery disease in the Bypass Angioplasty Revascularization Investigation 2 Diabetes trial (BARI 2D). Methods and results: Changes in adipokine levels were compared in patients with type 2 diabetes mellitus and coronary artery disease randomized to IS ( n = 1037) versus IP ( n = 1019) treatment strategies in BARI 2D. Circulating concentrations of leptin, adiponectin, monocyte chemoattractant protein-1, tumor necrosis factor-alpha, interleukin 6 and C-reactive protein were evaluated at baseline and one year. IS and IP treatment strategies exerted significant ( p < 0.0001) differential effects on: leptin (IS: 0.02% decrease, p = 0.01; IP: 13% increase, p < 0.0001); adiponectin (IS: 73% increase, p < 0.0001; IP: no change, p = 0.52); interleukin 6 (IS: 14% decrease, p < 0.0001; IP: no change, p = 0.68). Changes in monocyte chemoattractant protein-1 and tumor necrosis factor-alpha were not statistically different between groups. C-reactive protein decreased, but the effect was significantly greater in the IS group (–32%, p < 0.0001) than in the IP group (–5%, p = 0.0005). Conclusion: The IS and IP treatment strategies exerted divergent effects on adipokine and inflammatory profile in patients with type 2 diabetes mellitus and coronary artery disease. The IS treatment strategy-induced changes may be more favorable than the IP treatment strategy regarding cardiovascular pathophysiology.